The complete mitochondrial genome of cultivated radish WK10039 (Raphanus sativus L.). (3rd March 2016) - Jeong, Young-Min; Chung, Won-Hyung; Choi, Ah Young; Mun, Jeong-Hwan; Kim, Namshin; Yu, Hee-Ju
Abstract: We determined the complete nucleotide sequence of the mitochondrial genome of radish cultivar WK10039 ( Raphanus sativus L.). The total length of the mtDNA sequence is 244, 054 bp, with GC content of 45.3%. The radish mtDNA contains 82 protein-coding genes, 17 tRNA genes, and 3 rRNA genes. Among the protein-coding genes, 34 encode proteins with known functions. There are two 5529 bp repeats in the radish mitochondrial genome that may contribute to DNA recombination resulting in at least three different forms of mtDNA in radish.